Maternal Active Listening to Children's Daily Stories: Associations with Early Literacy and Social Development - Inten, Dinar Nur; Lichandra, Funny (THUFULA, 2026)
Parenting communication is often dominated by one-way instruction, marginalizing the crucial role of the mother as an active listener. This study aims to analyze the communication strategies of mothers when listening to children's narratives and their contribution to literacy and early socialization. The study used a quantitative approach with a survey method of 238 mothers who had early childhood (4-6 years) in Bandung Regency, which was dominated by housewives (71.8%) and high school educated (54.2%). Data collection used a questionnaire of three main dimensions: communication strategy, literacy contribution, and early socialization. The results showed that the strategy of active listening through providing positive responses and open-ended questions ("Then what?") was the most dominant strategy implemented with a high percentage of approval (64.3% Strongly Agree). This strategy contributes significantly to literacy, where 95.8% of respondents admitted that there is an increase in the richness of children's vocabulary. In terms of socialization, this routine has been proven to be effective in strengthening emotional relationships (62.6% Strongly Agree) and helping to reduce tantrums in children. In conclusion, listening to children's daily stories is an effective stimulation method that strengthens emotional relationships while building a child's academic and social foundation